1973
DOI: 10.1159/000148841
|View full text |Cite
|
Sign up to set email alerts
|

Defective Virions of Herpes Simplex Viruses

Abstract: Serial undiluted passage of clonally purified herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) in 4 different types of cells resulted in (i) partial loss (84–98%) of infectivity and (ii) the appearance of a new DNA within the infected cells with a higher buoyant density in CsCl (p = 1.732 g/cm3) than that of HSV-1 (1.725 g per cm3) or that of HSV-2DNA (1.727 g/cm3). Serial diluted passages of these stocks restored the high infectivity titers with a concomitant loss of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…We wish to emphasize that minor fragments observed in digests of HSV DNAs cannot be attributed to the presence of defective DNA molecules of high buoyant density of the type reported by Bronson et al (9). The minor fragment patterns were highly reproducible and invariably present in all strains tested even after plaque purification, whereas the heavy density DNA appeared only after serial undiluted passaging and could be easily eliminated.…”
Section: Discussionmentioning
confidence: 58%
“…We wish to emphasize that minor fragments observed in digests of HSV DNAs cannot be attributed to the presence of defective DNA molecules of high buoyant density of the type reported by Bronson et al (9). The minor fragment patterns were highly reproducible and invariably present in all strains tested even after plaque purification, whereas the heavy density DNA appeared only after serial undiluted passaging and could be easily eliminated.…”
Section: Discussionmentioning
confidence: 58%
“…When HSV-1 is serially passaged at a high multiplicity of infection, virus stocks are produced which interfere with the infectivity of standard (non-defective) virus (Bronson et al, 1973;Murray et al, 1975 ;0000-6320 © 1985 (1984) suggested that these two signals may have to be on a contiguous DNA fragment for interference to occur, but the interpretation of their experiments is complicated by the fact that the defective genomes present within a virus stock generally represent a heterogeneous collection of molecules of incompletely defined sequence. In the present studies we have therefore attempted to extend these observations by using plasmids containing cloned copies of functional or inactivated ORIs and the viral 'a' sequence either alone or in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas recently plaque-purified virus stocks predominantly contain standard HSV genomes, defective virus populations obtained through serial undiluted propagation of such stocks have been shown to contain variable proportions of variant DNA molecules in which greater than 90% of the parental viral DNA sequences have been replaced by multiple head-totail reiterations of sequences derived from defined locations of the parental genome (9)(10)(11)(12)(13)(14)(15). On the basis of the origin of DNA sequences contained within their repeat units, defective HSV genomes have been divided into two classes.…”
mentioning
confidence: 99%